Working with Intuition. Issue 1 (24th January 2019) - NANGIA, ANISH
Abstract : Evidence, today, can have very narrow definitions. For digital products, this type of evidence usually includes clicks and engagement metrics. I believe that in our effort to only listen to numbers and data, we have created a culture that looks down on intuition as something messy and to be rejected. As a result, we train ourselves to cast our intuition aside. When we do listen, we dare not speak up about it. Intuition is a part of what makes us human. It is often the primary way we make sense of our work (and the world around us). Yet, we continue to focus only on rationality and logic. Ultimtately, the goal of this piece is to present intuition from a different lens – to understand it, learn to listen to it and create spaces where we talk about it.